Audio Speed Changer Application: Advancing Students’ Listening Comprehension - Nur Fadillah Nurchalis (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
As a receptive skill, listening is very influential for students' language development. Unfortunately, it often becomes the most challenging skill in learning a foreign language for students. One of the obstacles experienced by students of the English Study Program of STAIN Majene is the speed of spoken native language. This research aims to advance students' listening comprehension by using Audio Speed Changer (ASC). This research applied classroom action research of Kammis and Taggart model. It used four phases, namely planning, implementation, observation, and reflection. There were three instruments used in this research, namely listening test, observation sheet, and interview. The test was used to measure students' achievement. An observation sheet was used to identify speed development. An interview was used to gain information about students' responses to ASC application. There were two cycles in this research. The success of a cycle was determined by using two criteria as follow: (1) students' mean score had to be higher than 75 points in the last phase of a cycle; (2) there should be at least 80% of students who got at least 75 points for their final scores. This research found that students' scores dominated the poor category in the first cycle, but it reduced 35.32 points of its percentage in the second cycle. Students' scores in the second cycle dominated enough categories. ASC application was able to overcome one of the students' problems in listening comprehension.